Experimental study on mechanical properties of basalt fiber reinforced nano-SiO2 concrete after high temperature - Yang, Weidong; Liu, Huaxin; Wang, Hesong (Frontiers in Materials, 2024)
In enhancing the high-temperature resistance of concrete, incorporating fiber materials was established as an effective approach. This study focused on evaluating the cubic compressive strength, splitting tensile strength, prism compressive strength, and flexural strength of plain concrete, nano-SiO2 concrete, and basalt fiber nano-SiO2 concrete when subjected to elevated temperatures. Subsequently, a concrete strength prediction model was established, and a microstructure analysis of the specimens was conducted. The results indicated that after exposure to 800°C, the cubic compressive strength, splitting tensile strength, prism compressive strength, and flexural strength of basalt fiber-reinforced nano-SiO₂ concrete increased by 33.7%, 15.6%, 10.4%, and 17.2%, respectively, compared to plain concrete. Furthermore, the fitting values of the strength prediction model were all above 0.9. Microstructure analysis revealed that the filling effect of nano-SiO₂ made the concrete matrix denser, while the basalt fiber effectively restrained the formation of cracks in the concrete matrix. Additionally, nano-SiO₂ promoted the formation of hydrated calcium silicate from Ca(OH)₂(CH) and adhered to the basalt fiber, enhancing bonding and reducing the risk of concrete spalling.